DISTRIBUSI SPASIAL KEHILANGAN TANAH DAN KEHILANGAN KARBON ORGANIK TANAH OLEH ALIRAN PERMUKAAN DI DAS OYO - WICAKSONO, ADITYA PANDU ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Soil loss process is always followed by the loss of soil organic carbon. As the consequence, there is a disturbance on the global carbon cycle and on the soil fertility condition. This research aimed to assess the spatial distribution of soil and soil organic carbon loss and also to identify the most affecting factors of soil loss such as slope, rain erosivity, soil erodibility, and land conservation, and crop management. Spatial distribution of the soil and organic loss potential is essential to be identified in order to determine the efficient land conservation. The research was conducted in 13 sub-watershed of Oyo Watershed. The research combined USPED and Staar methods to obtain reliable soil and organic carbon loss estimation. The Staar method was used to estimate the soil carbon loss suspended in the river. The USPED soil loss estimation was validated by the actual soil loss which was measured from erosion features found in the research area. Whereas, total soil organic carbon loss was validated with rating curve of organic carbon contained in the sediment suspension. The most affecting factor of soil loss was defined by using sensitivity analysis. The USPED soil loss was estimated to approximate the actual soil loss and was proved by 89% of accuracy level. Munggur sub-watershed experienced the highest soil loss by 5289.3 tons/year and soil organic loss by 165.79 tons/year. Whereas, soil loss in the entire Oyo watershed was estimated at 4207.9 tons/year followed by 2555.89 tons/year of soil organic loss. The soil loss which takes place in Oyo Watershed has depleted the soil organic up to 48.98%. The research found out that conservation and crop management was the most affecting factor to soil loss. Sensitivity analysis conducted for Munggur Sub-watershed has shown that the value of land conservation and crop management was 0.2 higher than the other two factors, i.e. slope and soil erodibility. It was concluded that land conservation and crop management was the most affecting factors for the soil and soil organic carbon loss.